Evaluación de la aplicación de cinco dosis de microorganismos eficientes, para el control de Pythium sp. y Fusarium sp. en el cultivo de lechuga (lactuca sativa) variedad great lakes 659 en Lamas – San Martin - Chavez Rios, Gilbert (2012)
This research paper entitled "Evaluation of the implementation of five doses of efficient microorganisms for the control of Pythium sp. and Fusarium sp. in the cultivation of lettuce (Lactuca sativa) variety Lamas Great Lakes 659 - San Martin ", was to assess and analyze the effect of the ME, and to determine the most appropriate dose of M.E Pitium control and sp Fusaium sp. We used the statistical design of randomized complete block design with four treatments and five blocks for a total of twenty experimental units. The results obtained indicate that all the treatments based on the application of different doses of efficient microorganisms, interacted in a synergistic and efficient manner and demonstrated their contribution in improving soil quality, improving crop growth and structural determinants were Pitium controlling Fusarium sp and sp., and increase photosynthetic processes and crop production of lettuce, variety Great Lakes 569 under conditions Lamas edafoecológicas district. Economic analysis of treatments reported that T1 (two liters of EM) was the most appropriate dose, it had the highest value of benefit / cost with in 0379 and the largest percentage yield (37.91%) slightly higher than T3 treatments, T4, T2 and T0 who obtained values of B / C of 0.375, 0.372, 0.340 and -95.10 respectively and thus lower profitability percentage values. Key Words: Microorganisms efficient Pitium, Fusarium, different doses, synergistic, Great Lakes, economic analysis.